Adroit Accountability or Keeping a Step Ahead - John G. Richardson; Joy Staton; Ken Bateman; Clayton E. Hutcheson (Journal of Applied Communications, 2000)
From its inception, the United States Cooperative Extension System has had a history of being accountable for its programs and funding. With accountability becoming of even greater importance, plans and proactive efforts must be undertaken to assure that useful program accomplishment information is made available to identified audiences in an aggressive manner. Yet, remaining continuously vigilant to the changing circumstances or political landscapes within a county or state is a critical must to assure that when questions of the value of Extension programs arise, its programs and budgets can withstand the scrutiny. Three case studies are described in which proactive measures have been undertaken to have program information readily available and provide needed accountability information in a timely manner to policy makers and citizens. Changing political directions in the county governments and their implications are explained. Significant accountability measures prior to certain policy shifts, during the stressful period that resulted, and following the shifts, resulted in strong Extension programs being able to cope with adversity or even to gain greater support. In circumstances of political tranquility or in periods of great change, a large measure of organizational risk can be avoided by keeping Extension's accountability a step ahead of inevitable changing circumstances.